EFEKTIVITAS PENINGKATAN PENGETAHUAN TERHADAP KONTRASEPSI MANTAP DENGAN METODE SNOWBALLTHROWING - Oktavianis Oktavianis; Amelia Sandra Meta (Maternal Child Health Care, 2022)
According to the World Health Organization (WHO) contraceptive use has increased in many parts of the world by 57.4%. West Sumatra Province has a total of 729,428 PUS with KB acceptors as many as 416,992 people in 2016. Solok District Health Office in December 2017 amounted to 59.79% of the total existing PUS with MOW contraceptive users as many as 59 people and MOP as many as 11 people.The purpose of this research was to determine the effectiveness in increasing knowledge of steadycontraception with the Snowball Throwing method in fertile age couples family planning acceptors inKayuJaoCommunity Health Center GunungTalangKabupatenSolok, 2018. The research used Pre Experimental method with One Group Pretest Posttest approach design. It was conducted in KayuJaoCommunity Health Center in GunungTalangKabupatenSolok in 2018 with 15 people as the samples. It was chosen by using PurposiveSamplingtechnique. The results of this research showed that the differenceaverage knowledge before and after was 1.667 with standard deviation 1.589. The highest score is -0.778 and the lowest value is -2.546. Moreover, statistical test results obtained that the effectiveness of knowledge increasing of steady contraception with Snowball Throwing method in fertile age couples family planning acceptors in KayuJaoCommunity Health Center had P= 0.001 (<0.05). The conclusion of the study is expected to health workers to further improve the strategy in providing counseling to the community by using interesting learning methods.Keywords        : Knowledge, Steady Contraception, SnowballThrowing, Family Planning